INVENTARISASI JENIS BURUNG PADA PERAIRAN PANTAI KELURAHAN LATERI, KOTA AMBON - Veince Benjamin Silahooy; La Eddy (TECHNO: JURNAL PENELITIAN, 2020)
Birds are an important component in an ecosystem. Birds can live in various types of habitats such as forests, grasslands and waters. For example, shorebirds are a type of bird whose life depends on coastal waters. The presence of shorebirds can be an indicator of the productivity of coastal waters. This research was conducted to inventory the species of birds in the coastal waters of the urban village of Ambon City. The results obtained as many as 10 species consisting of 7 families. The family with the highest number of individuals is Phalacrocoracidae (35%) while the proportion of species is fairly even (10-20%). The results of the analysis concluded a fairly good diversity and evenness index (H '= 1.99; E = 0.87) where there was no dominance of a particular species (D = 0.17).